2019
DOI: 10.1002/pad.1874
|View full text |Cite
|
Sign up to set email alerts
|

Do public sector organizations ensure labor ethics? Perspectives from ethics and workplace spirituality in Bangladesh's garment sector

Abstract: Summary The suppression of labor rights is a matter of serious concern in developing countries. Yet little is known about the role of public agencies in protecting the rights of underprivileged employees. Hence, this study aims to examine the reasons behind the persisting labor exploitation in private enterprises despite the presence of public governance and labor codes. Data was collected through in‐depth interviews as well as archives from different external and internal agencies of privately owned garment e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The study identified factors including multinational power, political influence, and institutional corruption which undermine public power and sustain unethical labor practices in Bangladesh. The authors discuss these issues and give recommendations for further studies (Uddin, Hossain, Fujimoto, & Ahmed, 2019). The third article is entitled “Changing the paradigm of disability from stigma to equity in university social work education in Kyrgyzstan” and is authored by Katsui, Kazakunova, and Mojtahedi.…”
Section: Contributions To This Special Issuementioning
confidence: 99%
“…The study identified factors including multinational power, political influence, and institutional corruption which undermine public power and sustain unethical labor practices in Bangladesh. The authors discuss these issues and give recommendations for further studies (Uddin, Hossain, Fujimoto, & Ahmed, 2019). The third article is entitled “Changing the paradigm of disability from stigma to equity in university social work education in Kyrgyzstan” and is authored by Katsui, Kazakunova, and Mojtahedi.…”
Section: Contributions To This Special Issuementioning
confidence: 99%
“…Chen et al (2017) conducted a systematic review on supply chain collaboration towards sustainability, illustrating a lack of consideration about social concerns such as child labor and personal development. Likewise, Uddin et al (2019) reported unequal relationship with suppliers to attain economic motive from the perspective of public service ethics.…”
Section: Introductionmentioning
confidence: 99%